Effect of external prestressing strands on the Yielding Stage behaviours of steel beams. (February 2020) - Mahmoud, Kamal Sh.; Yousif, Mustafa A.; Rasheed, Mohammed M.
Abstract: Seven steel beams were tested under one point load to investigate the effect of existence of external prestressing strands on the behavior of steel beams at yielding stage. All steel beams have the same gross area, overall length and the strengthened specimens are employed by two low relaxation strands. The steel beams are divided into two groups according to existence of prestressing strands, the first group involves one steel beam which is considered as a reference beam, while, the second group involves six specimens divided according to the location of prestressing strand (e) at jacking stress (fpj =1120.061 MPa). During the tests, it can be noted that the load strain response for strengthened steel beams are stiffer and the increasing percent of stiffening increases with the increasing of strand eccentricity and the maximum yielding load of strengthened tested beams increases with the increasing of strand eccentricity and the maximum enhancement in yielding load of strengthened tested beams reaches to 126.331% in the OM234 sample compared with the reference beam. Also, it was found that the yielding strain positions changed from bottom flange to the top region for the strengthened tested beams as compared with the reference steel beam and the increasing percent in the yielding to ultimate load ratio ( Py/Pu ) for the strengthened tested beams increases with the increasing of strand eccentricity at constant applied jacking stress. The maximum percentage increase in yielding to ultimate load ratio (Py/Pu) of strengthened tested beams reaches to 21.06% in the Straight strand profile as defined by OM234 sample as compared with the reference beam.